Surface analysis of Metrohm BT220 screen-printed electrodes through electrochemical techniques: importance of pretreatment - Khor, Chun Keat; Denker, Sherab; Ignaszak, Anna (Frontiers in Chemistry, 2025)
The pandemic that happened a few years ago has made many people aware of the importance of early detection for diseases. Hence, interest in research topics related to biosensors development, especially for point-of-care devices, is as high as it can be. To develop an electrochemical biosensor that meets technical requirements such as miniaturization and compactness in a single piece, many researchers have transitioned from a classical three-electrode system with the typical glass electrochemical cell equipped with large and separated electrodes to screen-printed electrodes (SPEs) and their corresponding accessories, allowing for small sample volume. Gold SPEs can be easily fabricated in large quantities and modified with various biological molecules through the formation of self-assembled monolayers, providing extremely sensitive responses to electrochemical signals and making them an attractive candidate for biosensor designs. In this work, an important pretreatment step, electropolishing in sulfuric acid, was investigated for gold SPE supplied by Metrohm, product BT220. Electrochemical capacitance spectroscopy (ECS) was employed to determine capacitance, which was correlated with changes in surface area, thereby providing insight into how various parameters of cyclic voltammetry (CV) used in electropolishing influence the reproducibility of the pre-treatment process. To optimize the electropolishing process of gold SPE, we have found that (a) the number of CV cycles during electropolishing should be set to ensure that all electrodes reached the same gold reduction peak current, which provides both the very low RSD for electrochemical quantitate of a baseline electrode (i.e., capacitance and active surface area below 2.9% and 1.9%, respectively) (b) the reference electrode incorporated in SPE is not stable in ferricyanide/ferrocyanide solutions, which are frequently used as a standard redox probe in electrochemical biosensors; and (c) this type of SPE should not be used in solutions containing ethanol, the solvent commonly used to dissolve thiolate blocking agents. This analysis provides insight into how to optimize the SPE’s pre-treatment, ensuring the sensor platform is consistent and the surface is reproducible before biological modifications, which in turn yields more steadfast results for biosensor development.